Spatio-temporal variation of soil microplastics as emerging pollutant after long-term application of plastic mulching and organic compost in apple orchards. (1st July 2023) - Wang, Yuanji; Liu, Li; Cao, Shan; Yu, Jing; Li, Xiangyu; Su, Yating; Li, Gaochao; Gao, Hua; Zhao, Zhengyang
Abstract: Microplastics (MPs) pollution in agroecosystems have aroused great alarm and widespread concern. However, the spatial distribution and temporal variation characteristics of MPs in apple orchards with long-term plastic mulching and organic compost input are still poorly understood. This study investigated MPs accumulation characteristics and vertical distribution after applying plastic mulch and organic compost in apple orchards for 3 (AO-3), 9 (AO-9), 17 (AO-17), and 26 (AO-26) years on the Loess Plateau. The clear tillage (no plastic mulching and organic composts) area was used as a control (CK). At a soil depth of 0–40 cm, AO-3, AO-9, AO-17, and AO-26 treatments increased the abundances of MPs, and the black fibers and fragments of rayon and polypropylene were dominant. In the 0–20 cm soil layer, the abundances of MPs increased with the treatment time; the abundance was 4333 pieces kg −1 after 26 years of treatment, gradually decreasing with soil depth. In different treatments and soil layers, the percentages of MPs <1000 μm were dominant (>50%). The AO-17 and AO-26 treatments significantly increased the MPs with the size of 0–500 μm at 0–40 cm and the abundances of pellets in 0–60 cm soil. In conclusion, the long-term (≥17 years) application of plastic mulching and organic composts increased the abundances of small particles at 0–40 cm, and plastic mulching contributed the most to MPs, while organic composts increased the complexity and diversity of MPs. Graphical abstract: Image 1 Highlights: Spatio-temporal variation and distribution of soil microplastics was studied. The abundances of Microplastics (MPs) at topsoil increased with the treatment time. Long-term treatments significantly increased the MPs of sizes 0–500 μm and pellets. MPs distribution in different soil layers were disordered under short-term treatment.